2010
DOI: 10.1021/bm901215s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Gene Delivery of Poly(amido amine)s with Different Branched Architecture

Abstract: A general strategy to improve the transfection efficiency as well as lower the cytotoxicity for polycationic vectors has been developed. Through the polycondensation addition of N,N'-methylene bisacrylamide and 1-(2-aminoethyl)piperazine in a water/N,N-dimethylformamide cosolvent, a series of cationic poly(amido amine)s with same repeating units but different branched architecture have been prepared. With the increase in branched architecture, the cationic polymers become more and more compact, accompanied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 54 publications
0
82
0
Order By: Relevance
“…4,16 Each sample solution (0.2 mg/mL) was prepared in 30 mL of an aqueous NaCl solution (0.15 mol/ mL). The sample solutions were initially titrated with a 0.1 mol/mL NaOH solution to a pH of 10.0.…”
Section: Buffer Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…4,16 Each sample solution (0.2 mg/mL) was prepared in 30 mL of an aqueous NaCl solution (0.15 mol/ mL). The sample solutions were initially titrated with a 0.1 mol/mL NaOH solution to a pH of 10.0.…”
Section: Buffer Capacitymentioning
confidence: 99%
“…21 Therefore, the result may indicate that pDNA-binding and -condensation abilities are enhanced with the increase in the fraction of branching units of the hyperbranched polysaccharide derivatives, in agreement with the literature. [4][5][6][7] This is closely related to their genedelivery efficacy, which needs to be investigated in the future.…”
Section: Buffer Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Dendrimers (Scheme 1) are also unique synthetic macromolecules of nanometer dimensions with a highly branched structure and globular shape with strong affinity towards DNA and RNA complexation [4][5][6][7][8][9][10]. It has been shown that synthetic polymers induce significant changes in DNA and RNA solubility and structure under given conditions [8][9][10][11][12][13][14][15][16][17][18][19][20]. Synthetic polymers are also used to transport miRNA and siRNA in vitro [11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that synthetic polymers induce significant changes in DNA and RNA solubility and structure under given conditions [8][9][10][11][12][13][14][15][16][17][18][19][20]. Synthetic polymers are also used to transport miRNA and siRNA in vitro [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. PEGylation of synthetic polymers such as dendrimers is shown to reduce toxicity and increase biocompatibility and DNA Transfection [6,7,9].…”
Section: Introductionmentioning
confidence: 99%